Motivations for sexual behavior and intentions to use condoms: development of the Regulatory Focus in Sexuality (RFS) Scale - Rodrigues, D. L. (2019)
Despite recurrent eforts to prevent sexually transmitted diseases through the use of condoms, HIV infections are still prevalent across Europe. Recent research framed by the regulatory focus theory has shown that prevention (vs. promotion)-focused individuals are more likely to adopt strategies to protect their health. Therefore, these individuals should also be more motivated to use condoms, because they are more likely to perceive greater health threats. In two cross-sectional preregistered studies (combined N = 520 Portuguese participants; databases available at https://doi.org/10.17605/osf.io/nzkmn), we developed the new Regulatory Focus in Sexuality (RFS) scale (Study 1), and tested if the association between prevention focus and intentions to use condoms was mediated by the perception of health threat (Study 2). Results from Study 1 suggested that the scale is valid and reliable. Results from Study 2 showed, as expected, that a predominant focus on prevention was associated with more condom use intentions with casual and regular sexual partners, because individuals perceived greater threat to their health. Additional exploratory analyses further showed that this mediation occurred only for individuals without a romantic relationship and was independent of how salient the condom use norm was. In contrast, for romantically involved individuals, there was no evidence for the mediation by perceived health threat. Instead, a predominant focus on prevention was positively associated with condom use intentions with the regular partner, but only when the condom use norm was more salient. Taken together, these results emphasize the importance of examining individual motivations for safe sex practices.